A critical assessment of the animator's artistic ownership over motion captured performances - Sarfo-Boansi, Emmanuel (My University, 2014)
The intention of this research report is to critically assess, as well as theoretically expand upon, the increasingly contentious area regarding character performance in computer generated (CG) animation for feature films that utilize motion capture technology. This paper specifically aims to investigate whether or not the use of motion capture in live-action visual effects, in the pursuit of creating CG characters that are as realistic as possible, has eroded the artistic autonomy of character animators and their artistic ownership of the performances of these characters. Through the analysis and comparison of pertinent case studies, it should become apparent that this perception is not absolute, and is largely dependent on the kinds of characters intended to be portrayed and the kind of film that they are to be portrayed in. It will be shown that motion capture can be a very effective collaborative tool not only in the relationship between directors and actors, but also between animators and actors under the creative supervision of directors.